2008
DOI: 10.1007/s11661-008-9594-2
|View full text |Cite
|
Sign up to set email alerts
|

On Factors Affecting the Phase Transformation and Mechanical Properties of Cold-Rolled Transformation-Induced-Plasticity–Aided Steel

Abstract: Two Mo-Nb microalloyed transformation-induced-plasticity (TRIP) steels, with Al contents of 0.23 and 0.65, were subjected to several hot-rolling conditions designed to generate different ferrite morphologies and grain sizes. These structures were then cold rolled and TRIP annealed under different heat-treatment conditions. To further develop TRIP steel in terms of strength and ductility, stabilizing retained austenite by isothermal bainitic transformation was studied in detail. Microstructure observation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The main advantage of aluminumalloyed TRIP steels over silicon-based compositions is that they do not form surface oxides, which improves coatability and galvanizing properties [19]. Generally, the carbon concentration in RA is higher in aluminum-alloyed TRIP steels, which is expected to increase its mechanical stability [1,20,21]. However, it has also been reported that there is no difference in carbon enrichment of RA between silicon-alloyed vs. aluminum-alloyed TRIP steels [22].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of aluminumalloyed TRIP steels over silicon-based compositions is that they do not form surface oxides, which improves coatability and galvanizing properties [19]. Generally, the carbon concentration in RA is higher in aluminum-alloyed TRIP steels, which is expected to increase its mechanical stability [1,20,21]. However, it has also been reported that there is no difference in carbon enrichment of RA between silicon-alloyed vs. aluminum-alloyed TRIP steels [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing aluminum would result in increasing the stronger ausferrite on the expense of retained austenite (Soliman and Palkowski, 2008). This can justify the hardness increase with increasing the aluminum as shown in Fig.…”
Section: Hardness Propertiesmentioning
confidence: 89%
“…10 that the time required for the end of stage I transformation decreased by increasing Al when applying Schedule I. This can be attributed to the effect of aluminium in accelerating the ausferritic transformation kinetics (Soliman and Palkowski, 2008) It is also obvious from Fig. 10 that, when applying Schedule I, deforming the DI resulted in accelerating the transformation.…”
Section: Ausferrite Formationmentioning
confidence: 89%
See 1 more Smart Citation
“…Pre-rolling, using dynamic recrystallization and finishing rolling at temperature levels closely above Ac3, promotes a non-recrystallized austenite condition, which provides a high nucleation density for ferrite formation. These facts result in ferrite grain sizes in the range of some microns [7,14]. Common concepts for TM rolled HSLA steels are shown in Fig.…”
Section: Thermomechanically Controlled Processing-a Success Storymentioning
confidence: 99%